2014
DOI: 10.1016/j.nmd.2013.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Performance of Upper Limb assessment in Duchenne muscular dystrophy

Abstract: The Performance of Upper Limb was specifically designed to assess upper limb function in Duchenne muscular dystrophy. The aim of this study was to assess (1) a cohort of typically developing children from the age of 3years onwards in order to identify the age when the activities assessed in the individual items are consistently achieved, and (2) a cohort of 322 Duchenne children and young adults to establish the range of findings at different ages. We collected normative data for the scale validation on 277 ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(119 citation statements)
references
References 12 publications
7
110
1
1
Order By: Relevance
“…77,78 In older individuals who are non-ambulatory, the Brooke Upper Extremity Scale, Egen Klassifikation scale, and elbow flexion and grip strength are responsive to change over 1–2 years, 57,79,80 with testing now including reachable workspace 52,81 and assessment of upper limb function (performance of upper limb test). 51,53,58 …”
Section: Rehabilitation Managementmentioning
confidence: 99%
“…77,78 In older individuals who are non-ambulatory, the Brooke Upper Extremity Scale, Egen Klassifikation scale, and elbow flexion and grip strength are responsive to change over 1–2 years, 57,79,80 with testing now including reachable workspace 52,81 and assessment of upper limb function (performance of upper limb test). 51,53,58 …”
Section: Rehabilitation Managementmentioning
confidence: 99%
“…In comparison, other studies have reported yearly declines in 6MWD ranging between 10 and 57m. 3537 Even in this young, highly functional group of boys, MR biomarkers were highly responsive to disease progression over 12 months. Notably, we found that even in boys whose 6MWD improved or remained stable over 12 months, a significant increase in FF and MRI-T 2 was noted, indicating that MR biomarkers can detect subclinical disease progression.…”
Section: Discussionmentioning
confidence: 91%
“…Following MR data acquisition, subjects completed the Performance of Upper Limb test (PUL) as previously described [14, 16], the Brooke Upper Extremity Scale [5], and grip and pinch strength testing using a Jamar handgrip dynamometer [13]. …”
Section: Methodsmentioning
confidence: 99%